Dilated cardiomyopathy in pregnancy: a case report - Jagadeesan, Nithya; Peruvankuzhiyil, Thasneem (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
The prevalence of dilated cardiomyopathy (DCM) is 1:2500 among the women of childbearing age. DCM often develops during second trimester or may be present prior pregnancy. We report a successful pregnancy outcome in a young pre-eclamptic woman with DCM who presented with cardiac failure. Multidisciplinary team involved. Anti-failure drugs, antihypertensives and thromboprophylaxis administered. Caesarean section was performed at 30 weeks because of spontaneous onset of labour to avoid undue stress on failing heart. Intra operative and post-operative recovery was uneventful. Follow up showed improvement in ejection fraction. Counselling prior pregnancy, stable cardiac status, regular monitoring, personalised care ensures safe maternal and foetal outcome.